A Cross-Sectional Study Assessing Medication Adherence to Diabetes Mellitus Treatment Among Adults in A Tertiary Care Hospital in the National Capital Region, Delhi - Prem Kumar; Anshu Singh; Mahak Lamba; Muskan Garg (National Journal of Community Medicine)
Introduction: India has earned the dubious distinction of being the diabetic capital of the world. Poor adherence to diabetes treatment is common now a days that can lead to severe health complications and is related to increased morbidity and mortality. Keeping this in mind, the present study had been planned to assess medication adherence to diabetes mellitus treatment among adults in a tertiary care hospital.